The Application and Development of Static Pressure Air Floating in the Field of Micro-Low-Gravity Simulation Experiments for Spacecraft - Libin Zang; Weijie Hou; Lei Liu; Haixia Hu; Xingze Wang; Yong Jia; Yongbo Hao; Yuehua Li; Baoshan Zhao (Lubricants)
The force conditions experienced by spacecraft and astronauts in space are vastly different from those in Earth’s gravitational environment, hence it is necessary to conduct adequate micro-low-gravity environment simulation tests on the ground before launch. In this paper, an overview is provided of the current status of micro-low-gravity simulation test technology for spacecraft based on hydrostatic air-bearing. The paper systematically organizes the application of hydrostatic air-bearing technology in micro-low-gravity simulation tests, such as the deployment of space mechanisms, spacecraft GNC (Guidance, Navigation, and Control), on-orbit operations of space manipulators, and astronaut training. It summarizes the principles of air-flotation micro-low-gravity simulation technology in different scenarios and distills suitable solutions for various requirements. Finally, the paper looks forward to the development trends of air-flotation micro-low-gravity simulation test technology and proposes key technical challenges that need to be overcome in aerostatic bearing.